Patient-Reported Opioid Pill Consumption After an ED Visit: How Many Pills Are People Using?. Issue 2 (27th March 2020) - McCarthy, Danielle M; Kim, Howard S; Hur, Scott I; Lank, Patrick M; Arroyo, Christine; Opsasnick, Lauren A; Piserchia, Katherine; Curtis, Laura M; Wolf, Michael S; Courtney, D Mark
Abstract: Objectives: Recent guidelines advise limiting opioid prescriptions for acute pain to a three-day supply; however, scant literature quantifies opioid use patterns after an emergency department (ED) visit. We sought to describe opioid consumption patterns after an ED visit for acute pain. Design: Descriptive study with data derived from a larger interventional study promoting safe opioid use after ED discharge. Setting: Urban academic emergency department (>88, 000 annual visits). Subjects: Patients were eligible if age >17 years, not chronically using opioids, and newly prescribed hydrocodone-acetaminophen and were included in the analysis if they returned the completed 10-day medication diary. Methods: Patient demographics and opioid consumption are reported. Opioid use is described in daily number of pills and daily morphine milligram equivalents (MME) both for the sample overall and by diagnosis. Results: Two hundred sixty patients returned completed medication diaries (45 [17%] back pain, 52 [20%] renal colic, 54 [21%] fracture/dislocation, 40 [15%] musculoskeletal injury [nonfracture], and 69 [27%] "other"). The mean age (SD) was 45 (15) years, and 59% of the sample was female. A median of 12 pills were prescribed. Patients with renal colic used the least opioids (total pills: median [interquartile range IQR] = 3 [1–7]; total MME: median [IQR] = 20 [10–50]); patients with back pain used the most (total pills: median [IQR] = 12 [7–16]; total MME: median [IQR] = 65 [47.5–100]); 92.5% of patients had leftover pills. Conclusions: In this sample, pill consumption varied by illness category; however, overall, patients were consuming low quantities of pills, and the majority had unused pills 10 days after their ED visit.